Doppler tolerant modified P4 code (DTMP4 code) for pulse compression radar - De Jesus, Neon S.
Pulse compression refers to the design of a pulse waveform so that the ability of the radar in resolving two closely separated targets is improved. High resolution can be realized by using pulse compression waveform because of the narrow main lobe on its matched filter response, or equivalently, on its autocorrelation function (ACF). With narrow ACF main lobe, the radar can transmits wide pulse to increase the power of the signal reflected by the target. This improves the ability of the radar to detect object without compromising its range resolution. However, the appearance of sidelobes in the ACF must be address in the design of the waveform, that is, the sidelobes level (SLL) must be kept low to prevent masking of target with low return signal power. Additionally, the variation on the sidelobes and main lobe shape must be contained as the velocity of target increases to maintain the good detection and resolution performance of the radar, that is, the pulse compression waveform must be Doppler tolerant. In this study, a new pulse compression waveform called Doppler Tolerant Modified P4 Code (DTMP4 Code) is presented and analyzed. The waveform was generated by modulating a pulse using linear frequency modulation (LFM) then applying phase coding (P4 Code) to the resulting waveform. The waveform can be designed to have high resolution and low ACF SLL. Simulation results show that the resolution of the DTMP4 code increased when the time-bandwidth product (BT product) was increased. In addition, the increased in codelength, M, resulted in the reduction of the ACF SLLs. Comparing the results of the velocity estimation, the DTMP4 code outperformed the P4 code and LFM in resolving closely spaced multiple moving targets. Moreover, it was found that the proposed waveform is less affected by the Doppler shift compared to P4 code. Further test showed that, by using CFAR algorithm, the DTMP4 code had high probability of detection even at low SNR and high Doppler shift.